Kwara-Central undergraduates’ perceived peer pressures on youths involvement in kidnapping - Rasheed Adewuyi Shofiu; Abdulaziz Isiaka (Journal of Education and Learning (EduLearn), 2021)
This study examined Kwara central undergraduates’ perceived peer pressure on youths’ involvement in kidnapping. This study was a descriptive survey. The population comprised of all undergraduates in Kwara Central Senatorial District. The target population was undergraduates from University of Ilorin and Alhikmah University, 500 students were randomly selected. A researcher design questionnaire was used for data collection while data collected were analyzed using frequency and percentage, mean, standard deviation (SD), ranking T-test and one-way analysis of variance. Research hypotheses were tested using independent T-test and also one-way analysis of variance at 0.05 level of significance. Findings revealed that peer pressure influences youth involvement in kidnapping in Nigeria; there was no significant difference in the influence of peer pressure on youth’s involvement in kidnapping as perceived by undergraduates based on academic level and school type. It was concluded that peer pressure influences youths’ involvement in kidnapping in Nigeria. We recommend both school and home adequate monitoring of students peers and friends at home and schools to prevent them from bad groups, adequate legislation to curb youth participation in kidnapping, good leadership examples for young ones to emulate and value reorientation of youths should be given top priority in educational curriculum.